First Order Assessment of Heat Transfer due to the Loss of Inventory in a Spent Fuel Pool - Fillis, Vernon W (Department of Chemical Engineering, 2019)
The Fukushima Daiichi Nuclear Power Plant accident created renewed international interest in the behaviour of spent fuel subsequent to a complete loss of water inventory in a spent fuel pool (SFP). The study conducted in this dissertation serves as a starting point in gaining an understanding of the thermal hydraulics and associated heat transfer processes involved when spent fuel assemblies (SFAs) become uncovered in air. The complete loss of cooling in a SFP is a complex 3-D problem, hence several simplifications were necessary in this research to narrow the scope. Further, due to the complexity of this topic, the results obtained serves purely as a first order approximation. Accordingly, the Flownex systems CFD code (version 8.6.1.2630) was used to simulate the thermal response of the uncovered SFAs in the SFP of a typical Pressurised Water Reactor (PWR) during a severe accident scenario. Two network models were developed. The first was to identify the dominant heat transfer mechanisms with-in the spent fuel pool and it therefore accounted for a range of physics. This included convective heat transfer through the composite SFA channel walls, conduction along the vertical axial direction of the SFAs and through the inner and outer rack wall as well as through the fuel building (FB) roof and side walls. The model also took into account the radiative heat transfer from the cladding surface of the composite SFAs to the FB roof and side walls. This network model informed that the heat transfer with-in the SFA during the considered extreme accident scenario is dominated by radiative heat transfer. This informed the development of an improved 2-D network model using conduction elements which were specially calibrated in this work to account for radiative heat loss. An effective conduction for the fuel volume which is dependent on temperature was determined and was used to assess the severe accident. Transient results showed that the spent fuel may reach cladding oxidation temperature within circa 10.5 hrs after a complete loss of inventory.